PENGARUH MOTIVASI, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA BUMDES EKA BUDI SAKTI DI DESA SERAYA - Ni Made Eka Kristianti; Ni Luh Anik Puspa Ningsih; Ni Kadek Sioaji Yamawati (Warmadewa Management and Business Journal (WMBJ), 2024)
As a Village-Owned Enterprise (BUMDES) it has an important task in optimizing village potential in order to realize village development. This research aims to determine the influence of motivation, work discipline and work environment on employee performance at BUMDES Eka Budi Sakti in Seraya Village. The research uses quantitative data types. The sampling method used a saturated sampling technique, with a sample size of 41. The analysis method used was multiple linear regression analysis with the help of the SPSS version 26.0 for Windows program. Based on the research results, it was found that motivation has a significant positive effect on employee performance, work discipline has a significant positive effect on employee performance, the work environment has a significant positive effect on employee performance and employee performance at BUMDES Eka Budi Sakti in Seraya Village is influenced by motivation, work discipline and the environment the remaining work is influenced by other variables